Zlatni standard – oličenje odgovornosti države u međunarodnom pravu životne sredine - Bărbat, Vlad (Glasnik Advokatske komore Vojvodine, 2025)
This present article examines how the right to a healthy environment became a human right and how it was internationalized in response to the idea that transboundary damage existed. This evolution of the Environmental right’s study and regulation led to the creation and growth of International Law concerning the Environment. In a second part, the article focuses on the key features of this institute (the right to a healthy environment) and its academic place within the environmental field and focuses on the international responsibility of the State when violating a regulation and damages the right of another sovereign State or territorial area outside its national jurisdiction. Thirdly, we highlight the diverse but similar State responsibilities by investigating this type of state accountability as a foundational idea of international environmental law and illustrate how its support for a number of international standards helps nations come together on a worldwide scale to work toward sustainable development and the recovery of the terrestrial environment. Lastly, we seek and addresses how these two categories of state duty enable global environmental conservation.